Calorimetric analysis of the crystallization of PBT considering the dynamic cooling condition of real processing. (May 2020) - Heidrich, Dario; Gehde, Michael
Abstract: The crystallization behavior of polymers is usually investigated by the Differential Scanning Calorimetry (DSC) under isothermal or non-isothermal conditions, the latter one at constant cooling rates. The results of such experiments are used to calculate the crystallization during the dynamic cooling of processing, for instance with the Nakamura crystallization model. In contrast, in this article the crystallization of Polybutylene Terephthalate (PBT) was measured directly calorimetrically at dynamic cooling. For this purpose, the Fast Scanning Calorimetry (FSC) was used in particular, which can perform fast changes in scan rates. With this new approach, for example, the crystallinity can be determined across the part thickness, without calculating it with a crystallization model. At the same time, the subsequent melting behavior of structures formed during dynamic cooling was investigated. Thus a better interpretation of the first heating run of processed samples is possible. Highlights: Dynamic cooling approach for investigating the crystallization behavior of polymers. Process-related condition of crystallization. Conclusions on geometric influences on the crystallization are possible. Quantitative evaluation of bimodal crystallization within the part. Perspective as experimental validation of the Nakamura model conceivable.